Dietary inflammatory index in relation to incident CKD: A prospective study of UK Biobank participants - Qian Yang; Queran Lin; Yixi Liu; Pufei Bai; Suhua Gao; Xin Lv; Saijun Zhou; Hongyan Liu; HaiZhen Sun; Pei Yu (PLoS ONE, 2026)
Background and objectives The relationship between increased inflammatory diet patterns and chronic kidney disease (CKD) remains unknown and has not been investigated in large cohorts. Methods A total of 154,070 adults registered in UKB database were enrolled and followed, free of CKD and eGFR > 90 mL/min/1.73 m2 at baseline. The energy-adjusted dietary inflammatory index (E-DII) was evaluated using the 24-h recall diet. Cox proportional hazards regression models were used, adjusting for confounders such as demographic indicators, socioeconomic status, and lifestyle factors. Additionally, a subgroup analysis was conducted to investigate the relationship with incident CKD. The nonlinear relationship between E-DII and CKD risk was analyzed using a restricted cubic spline. Results During a median follow-up of 11.4 years, 3402 (2.21%) cases occurred. After adjustment for all potential confounders, a higher E-DII was associated with an increased risk of incident CKD (HR for 1 unit increment: 1.05 (1.00–1.10), p = 0.034). According to the result of the restricted cubic spline, when E-DII > 1.857, the risk of early-stage CKD would increase significantly. Conclusions A higher pro-inflammatory diet was associated with an increased risk of early-stage CKD in the fully adjusted model. An anti-inflammatory diet may serve as a potential preventive strategy for early-stage CKD, although causal inference cannot be established from this observational study.